MXene-supported stable adsorbents for superior CO2 capture. Issue 21 (20th May 2021) - Liu, Fa-Qian; Liu, Xin; Sun, Lishui; Li, Rongxun; Yin, Chun-Xiao; Wu, Bozhen
Abstract : Ti3 C2 (OH) x –polyethyleneimine-1, 2-butylene oxide (Ti3 C2 /PEI/BO) nanocomposite with superior CO2 capture performance. Abstract : Polyamine-based solid adsorbents are promising candidates for CO2 capture, but long-term stability under practical regeneration conditions (100% CO2 at 120 °C) remains the biggest hurdle. In this paper, we prepared MXene-supported adsorbents with excellent long-term stability by combining two strategies. First, 1, 2-butylene oxide (BO) with an epoxy group was grafted onto polyethyleneimine (PEI) to suppress the formation of urea. Second, Ti3 C2 (OH) x MXene was used as the support of polyamines to improve the wear resistance and thermal conductivity. The prepared MXene-supported adsorbents exhibit a large working capacity (2.6 mmol g −1 ) and a very stable cycling stability because of the synergetic effect. The adsorbents also exhibit a very low regeneration heat of 1.90 MJ per kg (CO2 ) and a high mechanical stability against attrition (0.26% after 5 h time-on-stream). Thus, these MXene-supported adsorbents make the CO2 capture process promising.